3D conjugated systems based on a twisted quaterthiophene core as hole-transporting materials. Issue 35 (31st August 2016) - Yassin, Ali; Demeter, Dora; Roncali, Jean
Graphical abstract: Highlights: 3D systems with four carbazole and dithienopyrrole units fixed on a quaterthiophene. Large improvement of hole-mobility compared to bithienyl side groups. Increase of the conversion efficiency of the resulting organic solar cells. Abstract: 3D conjugated architectures built by attaching four peripheral bithienyl, carbazole, and dithienopyrrole blocks on a twisted quaterthiophene core have been synthesized and evaluated as donor material in organic solar cells. Replacing bithienyl by carbazole and dithienopyrrole significantly increases the hole-mobility, thus a threefold increase of conversion efficiency correlated with a two-order of magnitude increase of the hole-mobility is observed for the dithienopyrrole compound.